Impact of tax havens on the global economy: Impact of tax havens on the global economy - Toborek- Mazur, Joanna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The paper addresses the issues of related to the functioning of tax havens and its impact on the social environment. The author draws attention to the sources of creation and reasons for maintaining tax havens, indicating the key factors conditioning their creation and provides examples of countries that apply tax haven policies. As a result of the analysis, a new examinations and conclusion was identified related to tax haven issues. The author draws attention to the sources of creation and reasons for maintaining tax havens, indicating the key factors determining their creation. The publication/article presents the result of Project no 062/ZIR/2024/POT financed from the subsidy granted to the Krakow University of Economics